2020
DOI: 10.3389/fphys.2020.00935
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Functions of Mitophagy and Potential Roles in Renal Disease

Abstract: Mitophagy is an evolutionarily conserved process to selectively remove damaged or unnecessary mitochondria via the autophagic machinery. In this review, we focus on recent advances in the molecular mechanisms of mitophagy and how mitophagy contributes to cellular homeostasis in physiological and pathological contexts. We also briefly review and discuss the crosstalk between mitophagy and renal disease, highlighting its modulation as a potentially effective therapeutic strategy to treat kidney diseases such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 154 publications
(231 reference statements)
2
43
0
Order By: Relevance
“…Thus, PINK1 accumulates at the mitochondrial outer membrane, where it recruits Parkin (an E3 ubiquitin ligase) from the cytoplasm to the surface of the mitochondria ( Xu et al, 2020 ). PINK1 phosphorylates and activates Parkin, which can then ubiquitinate mitochondrial membrane proteins ( Capasso et al, 2020 ; Villacampa et al, 2020 ; Zuo et al, 2020 ). This ubiquitination allows mitochondria to be recognized and swallowed by autophagic vesicles and wrapped in a double-layer membrane structure.…”
Section: Receptor-dependent and Receptor-independent Pathwaysmentioning
confidence: 99%
“…Thus, PINK1 accumulates at the mitochondrial outer membrane, where it recruits Parkin (an E3 ubiquitin ligase) from the cytoplasm to the surface of the mitochondria ( Xu et al, 2020 ). PINK1 phosphorylates and activates Parkin, which can then ubiquitinate mitochondrial membrane proteins ( Capasso et al, 2020 ; Villacampa et al, 2020 ; Zuo et al, 2020 ). This ubiquitination allows mitochondria to be recognized and swallowed by autophagic vesicles and wrapped in a double-layer membrane structure.…”
Section: Receptor-dependent and Receptor-independent Pathwaysmentioning
confidence: 99%
“…Mitophagy is a mechanism by which damaged mitochondria are eliminated within a cell after stress challenges. 186,187 It is regulated by, among others, PINK1 (PTEN-induced putative kinase 1) 28,188 and autophagy proteins microtubule-associated protein 1A/1B-light chain 3I (LC-3I) and p62 in proximal tubules. 188,189 Using rat as an FA-AKI model, Aparicio-Trejo et al 155 demonstrated that PINK1 and p62…”
Section: Impaired Mitophagymentioning
confidence: 99%
“…This disruption of mitochondrial homeostasis is linked with redox imbalance and oxidative stress accompanied with impairment of mitochondrial membrane potential and release of apoptosis stimulating factors such as cytochrome c and apoptosis inducing factor (AIF) [ 133 , 134 , 135 , 136 ]. These deranged mitochondrial dynamics, if left unattended or uncorrected, would eventually lead to accumulation of damaged mitochondria, which could overwhelm the mitophagy capacity that is regulated by key proteins such as PINK1 and Parkin [ 137 , 138 , 139 , 140 ], resulting in cell death and worsened diabetic kidney injury. Therefore, mitochondrial homeostasis and dynamics can also serve as targets for renal therapy in DKD.…”
Section: Redox Imbalance-linked Mitochondrial Dysfunction In Dkdmentioning
confidence: 99%